Fundamentals Of Ensuring Interdisciplinary Communication Of The Technology Training Curriculum (Journal of Pedagogical Inventions and Practices, 2024)
Ensuring the interconnection of the curricula of each type of education requires considering and ensuring the continuity and interconnection of the education system, from the point of view of the relationship between practice and theory, based on the relationship between the types and stages of education, as well as the relationship between subjects and topics.